TRANSITION FROM SAK ETAP TO SAK PRIVATE ENTITIES (SAK EP) AND PREPARATION OF FIRST-TIME CONSOLIDATED FINANCIAL STATEMENTS IN NON-PROFIT ENTITIES WITH GROUP STRUCTURE (CASE STUDY ON ABC FOUNDATION AND SUBSIDIARIES) - Satria Chandra; Hadi Wibowo (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study analyzes the transition from Financial Accounting Standards for Entities without Public Accountability (SAK ETAP) to Financial Accounting Standards for Private Entities (SAK EP) and its implications for the first-time preparation of consolidated financial statements at Yayasan ABC. Following the termination of SAK ETAP in 2024, management adopted SAK EP in 2025 and designated 1 January 2024 as the transition date to ensure comparability between reporting periods in accordance with transitional provisions issued by the Indonesian Institute of Accountants. This research employs a qualitative case study approach. Data were obtained through document analysis, semi-structured interviews, and observation of the financial reporting process to examine adjustments to accounting policies, preparation of opening balances, and the establishment of consolidation procedures. The findings indicate that the transition required retrospective adjustments affecting financial instruments, impairment of receivables, deferred tax recognition, and actuarial gains and losses recognized in other comprehensive income. These adjustments directly affected the opening net assets as of 1 January 2024. Furthermore, the mandatory requirement to prepare consolidated financial statements under SAK EP resulted in significant structural changes in financial reporting, including harmonization of accounting policies, alignment of chart of accounts, elimination of intercompany transactions, and reconciliation between nonprofit and profit-oriented reporting frameworks. This study demonstrates that the adoption of SAK EP in entities with subsidiary structures involves not only technical accounting adjustments but also systemic and organizational restructuring of financial reporting processes. The findings provide empirical evidence and practical guidance for foundations and private entities undergoing similar transitions while initiating consolidated financial reporting.